To investigate the risk perception of rural adult population in Chikhwawa District, TA Maseya, on wife inheritance as a driver to HIV transmission - Nthowela, Chancy Alfred (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.